Observational Study of Pulse Transit Time in Children With Sleep Disordered Breathing - Yanney, Michael P.; Prayle, Andrew P.; Rowbotham, Nicola J.; Kurc, Miguel; Tilbrook, Sean; Ali, Nabeel (Frontiers in Neurology, 2020)
Background:Pulse transit time (PTT) is a non-invasive measure of arousals and respiratory effort for which we aim to identify values that detect sleep disordered breathing (SDB) in children. We also compare the sensitivity and specificity of oximetry with a multi-channel study. Methods:We performed a cross-sectional observational study of 521 children with SDB admitted for multi-channel sleep studies (pulse oximetry, ECG, video, sound, movement, PTT) in a secondary care centre. PTT data was available in 368 children. Studies were categorised as normal; primary snoring; upper airway resistance syndrome (UARS); obstructive sleep apnoea (OSA) and ‘abnormal other’. Receiver operator characteristic curves were constructed for different PTT (Respiratory swing; Arousal index) thresholds using a random sample of 50% of children studied (training set); calculated thresholds of interest were validated against the other 50% (test set). Study findings were compared with oximetry categories (normal, inconclusive, abnormal) using data (mean and minimum oxygen saturations; oxygen desaturations > 4%) obtained during the study. Results:Respiratory swing of 17.92ms identified SDB (OSA/UARS) with sensitivity: 0.80 (C.I. 0.62 – 0.90) and specificity 0.79 (C.I. 0.49 – 0.87). PTT arousal index of 16.06/ hour identified SDB (OSA/UARS) with sensitivity: 0.85 (95% C.I. 0.67-0.92) and specificity 0.37 (95% C.I. 0.17-0.48). Oximetry identified SDB (OSA) with sensitivity: 0.38 (C.I. 0.31 – 0.46) and specificity 0.98 (C.I. 0.97 – 1.00). Conclusions:PTT is more sensitive but less specific than oximetry at detecting SDB in children. The additional use of video and sound enabled detection of SDB in twice as many children as oximetry alone.